HUBUNGAN SOSIALISASI POLITIK DAN PARTISIPASI POLITIK TENTANG PEMILU SERENTAK 2018 DI PARIAMAN - megawati aliya octaputri; M. Fachri Adnan (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
The purposes of this research is to exlplains correlation between political socialization and citizen’s political participation on Pariaman Election on 2018. This research using quantitative descriptive method. Data were collected by questionarre. The population consists of all 59.245 voters using Proportionate Random Sampling. Respondents are counted by using Slovin with margin of error 5% and the result are 397 repondents. The result finding shows that there’s low correlation between political socialization with political participatin on Pariaman Election on 2018.